High performance polyurethane–polyacrylic acid polymer binders for silicon microparticle anodes in lithium-ion batteries. Issue 5 (2nd February 2022) - Niu, Sulin; Zhao, Min; Ma, Lei; Zhao, Fangfang; Zhang, Yu; Tang, Gen; Wang, Yue; Pang, Aimin; Li, Wei; Wei, Liangming
Abstract : Low cost and high-performance binder for silicon microparticle anodes. Abstract : As a potential anode material for lithium-ion batteries (LIBs), silicon (Si) has been widely studied because of its high capacity, appropriate potential and abundant sources. However, due to the huge volume changes of the silicon anodes during cycling, the capacity decays rapidly after a few cycles. As an important component of LIBs, polymer binders play a big role in alleviating the volume effect of silicon. The new binders developed at present could effectively improve the swelling problem of silicon, stabilize silicon anodes and improve the cycling stability of LIBs. Nevertheless, their synthesis usually involves complicated reactions. Moreover, it is a bigger challenge when a polymeric binder is used to stabilize cheap micro-silicon-particles. Herein, we present a simple process to prepare a three-dimensional polyurethane–polyacrylic acid network binder for silicon anodes by simply mixing readily available polyurethane and polyacrylic acid in water. This binder can effectively stabilize silicon anodes during cycling and improve the cycling stability of the silicon anodes. The capacity retention of the silicon anode is 70.3% after 200 cycles and 60.9% after 500 cycles, with a high specific capacity of 1934 mA h g −1 after 500 cycles, showing excellent electrochemical properties.